Analisis Karakteristik Materi Pelajaran Pendidikan Agama Islam di Jenjang SMK - Roy Setiawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
The comprehensive field of Islamic education encompasses not only all levels of schooling but also includes religion, ethics, history, law, and the Quran and Hadith. As part of Islamic religious education (PAI), students are taught to live in harmony with Allah, themselves, other humans, all living things, and the natural world, embodying the concept of Hablun Minallah wa Hablun Minannas. The main objective is to shape students' belief, understanding, and practice of Islamic teachings through planned learning activities, training, and guidance. Islamic religious education is an endeavor by educators to shape students' beliefs and practices via structured instruction, training, and guidance. This study explores the features of Islamic education resources across various educational levels, examining the types of instruction designed to identify these materials and evaluate their pros and cons. The study discovered that Islamic Religious Education (PAI) materials from different grade levels and educational types exhibit distinct characteristics. These differences include variations in content, weight, depth, as well as psychological, philosophical, sociological, and technological aspects. Understanding the characteristics of PAI materials at various educational levels is crucial for developing more effective, relevant curricula and teaching methods tailored to students' developmental needs. The findings of this study are also intended to serve as a reference for educators when developing PAI learning materials suitable for students' educational and developmental levels.